2020
DOI: 10.1101/2020.03.05.977884
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pex24 and Pex32 tether peroxisomes to the ER for organelle biogenesis, positioning and segregation

Abstract: Two Hansenula polymorpha ER proteins, Pex24 and Pex32, are tethers at peroxisome-ER contacts and function together with the peroxisomal protein Pex11. Their absence disturbs these contacts leading to multiple peroxisomal defects, which can be restored by an artificial tether. AbstractWe analyzed all four Pex23 family proteins of the yeast Hansenula polymorpha, which localize to the ER. Of these Pex24 and Pex32, but not Pex23 and Pex29, accumulate at peroxisome-ER contacts, where they are important for normal p… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
10
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 56 publications
4
10
1
Order By: Relevance
“…3 D ). In line with our earlier observations, peroxisome–ER contacts require Pex32 ( Wu et al, 2020 ). The distance between peroxisomes and ER increased in the absence of Pex32, whereas associations with the PM were unaffected in these cells ( Fig.…”
Section: Resultssupporting
confidence: 93%
“…3 D ). In line with our earlier observations, peroxisome–ER contacts require Pex32 ( Wu et al, 2020 ). The distance between peroxisomes and ER increased in the absence of Pex32, whereas associations with the PM were unaffected in these cells ( Fig.…”
Section: Resultssupporting
confidence: 93%
“…Similar observations have recently been made in the yeast Hansenula polymorpha [ 146 ]. This study revealed that the peroxins Pex24 and Pex32, which localize to the ER, function as tethers to mediate peroxisome-ER contacts ( Table 1 ).…”
Section: Peroxisome-organelle Interactions and Their Physiological Resupporting
confidence: 88%
“…While the functions of MOSPD2 are not clear and its effect on MCSs is not understood, it is possible that, like VAP proteins, MOSPD2 also interacts with ACBD4/5, so may represent a novel peroxisome-ER tether [ 16 ]. In yeast, the peroxins Pex3, Pex24, Pex32 and the inheritance protein Inp1 have been implicated in peroxisome-ER tethering (see Section 3.1.2 ) [ 3 , [146] , [147] , [148] ] ( Table 1 ).…”
Section: Peroxisome-organelle Interactions and Their Physiological Rementioning
confidence: 99%
See 2 more Smart Citations